The Analysis of Students’ Understanding of Electricity Fundamental Concepts - Mursalin Mursalin (STKIP Singkawang, 2022)
The aim of this research was to analyze students’ understanding of electricity fundamental concepts. The research of subjects are 86 students in physics department of UNG who are taking lectures of Fundamental Physics I in 2021/2022 academic year. Data analysis was conducted based on combination of multiple-choice test results Certainty of Response Index scores. The results show the students' understanding of electricity fundamental concepts which includes sub topics: conduction and induction, relation of electrostatic force and distance, electrostatic force resultant, electric field and electric potential, relation of voltage and electric current in conductor, series and parallel circuit, and placement of ammeter and voltmeter in electrical circuits, are still weak by most students, even many students who choose the false answer but are very sure of the answer. The research recommended further research to examine more intensely and more factually about the causes of student failure in solving fundamental problems of electricity, for example using Predict-Observe-Explain model or structured clinical interviews.